Ceramide Synthases Are Attractive Drug Targets for Treating Metabolic Diseases - Raichur, Suryaprakash (Frontiers in Endocrinology, 2020)
Ceramide synthases (CerS) are central enzymes required for the de-novo synthesis of ceramides and other sphingolipids. They catalyze the addition of different acyl-chains to a sphingoid base, and thus account for much of the rich diversity in the sphingolipid family. Recent studies have demonstrated that the acyl-chain is an important determinant of ceramide function, such that a small subset of ceramides (e.g., those containing the C16 or C18 acyl-chain) alter metabolism by inhibiting insulin signaling or inducing mitochondrial fragmentation. Herein I discuss the therapeutic potential of targeting certain ceramide synthase isoforms for the treatment of obesity, insulin resistance, steatohepatitis, and other metabolic disorders.